Challenges of Private Tour Operators of Assam: a study based on tour operators operating from India's Northeastern region - Sarmah, Biswajit (Turizam, 2021)
ABSTRACT:Assam, an important state of India’s Northeastern region, has a long history of hosting wildlife tours inside its world famous Kaziranga National Park since 1904. Kaziranga is famous for its largest concentration of One Horned Rhinoceroses and many other wild species amid its beautiful natural surroundings by the side of mighty river Brahmaputra. Assam also possesses Tiger and Elephant Reserves inside Manas National Park, which is famous for its rich bio-diversity. One of the world’s largest river islands- Majuli which is a cultural hotspot for tourists with academic interest is located in the central Assam. Centered around these natural locations and other man made religious and historical places of importance like Kamakhya Temple, Rang Ghar, Kareng Ghar etc. the tourism industry has developed in Assam.  At present, more than seventy recognized Private Tour Operators and one Government of Assam undertaking tour operator are providing valuable services to the tourists visiting Assam and other adjacent Northeastern States of India.The tourism industry has witnessed and acknowledges the role of tour operators as one of the principal intermediaries between the supplier of travel services and the tourists. But the progress of technology also brings new challenges along with many opportunities for the tour operators. These Private Tour Operators have to face many challenges while operating from the remotest part of India’s North East. Severe flood, landslide, terrorism, frequent strikes called by different organizations, underdeveloped infrastructure, external challenges, lack of capital for business - are some of the challenges with which the Tour Operators have to fight on regular basis. The rapid expansion of Internet and other social media platforms have gradually contracting the role of tour operators as the principal intermediary in the tourism industry.
Keywords: Private Tour Operators, Tourism, Assam, North East India, Kaziranga National Park, Package Tours.